Distribution of indigenous freshwater fishes in the central coastal region of Shertallai, Kerala - Jayasree, M; Sabesan, S; Krishnamoorthy, K; Panicker, K N (Indian Journal of Fisheries, 2011)
Use of indigenous fish species in the control of vector breeding is being encouraged due to their natural adaptation in a given area. Preliminary survey on the prevalence of fish species is a prerequisite lor the identification of potential larvivorous fishes and their association with other co-existing species. Such a survey was carried out in Shertallai taluk in Kerala State, to develop vector control strategies with larvivorous fishes in an integrated approach to contain Malayan filariasis, known to he endemic for many decades in the region (Rajagopalan et al. 1988).